Answer:
1/3
Step-by-step explanation:
V=x³-7x+6, V=(x-2)(x+3)*h
(x-2)(x+3)*h=x³-7x+6
h{x²+x-6}=x³-7x+6
h=(x³-7x+6)/(x²+x-6)
Therefore h=x-1
-----------------------------
Check answer:
V=(x-2)(x+3)(x-1)
=(x-1)(x²+x-6)
=x(x²+x-6)-1(x²+x-6)
=x³+x²-6x-x²-x+6
=x³-6x-x+6
=x³-7x+6
Answer:
= 5n - 2
Step-by-step explanation:
The nth term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Given a₄ = 18 , then
a₁ + 3d = 18 , that is
3 + 3d = 18 ( subtract 3 from both sides )
3d = 15 (divide both sides by 3 )
d = 5
Then
= 3 + 5(n - 1) = 3 + 5n - 5 = 5n - 2 ← explicit rule